Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Can the following integral integrated by parts?
$$\int\ln x\;\sin^{-1} x\, \operatorname d\!x$$

share|improve this question
    
Can you please explain how to do that? –  Swapnanil Saha Aug 14 '12 at 17:22
1  
@swapnanilsaha There should be an empty check mark next to answers to your questions. Clicking that will accept someones answer. Note that you can only accept one answer. –  Holdsworth88 Aug 14 '12 at 17:24
1  
@Holdsworth88 : Thankyou very much. –  Swapnanil Saha Aug 14 '12 at 17:26
1  
"Can the following integral integrated by parts?" - repeated use of it, yes. To start you out: $u=\arcsin\,x$, $\mathrm dv=\log\,x\mathrm dx$. –  J. M. Aug 14 '12 at 17:27

3 Answers 3

up vote 4 down vote accepted

Integration by parts formula

$$\int u(x)\underset{dv}{\underbrace{v^{\prime }(x)dx}}=u(x)v(x)-\int v(x) \underset{du}{\underbrace{u^{\prime }(x)dx}}.$$

If we apply the LIATE rule to

$$\int \ln x\arcsin x\,dx,$$

we should choose

$$u =\ln x,\quad dv=\arcsin x\,dx.$$

Normally there is a choice of the terms $u,v'$ of the integrand $uv'$ that makes integration much easier. However in the present case the other possible choice $u=\arcsin x,v'=\ln x$ leads to integrals of similar difficulties.

$$\begin{eqnarray*} I &=&\int \ln x\arcsin x\,dx, \qquad \text{(}v =\int \arcsin x\,dx\quad \text{see evaluation below)} \\ &=&\left( \ln x\right) \left( x\arcsin x+\sqrt{1-x^{2}}\right) -\int \frac{ 1}{x}\left( x\arcsin x+\sqrt{1-x^{2}}\right) \,dx \\ &=&\left( \ln x\right) \left( x\arcsin x+\sqrt{1-x^{2}}\right) -\int \arcsin x\,dx-\int \frac{1}{x}\sqrt{1-x^{2}}\,dx \\ &&\text{(see evaluation of the last integral below)} \\ &=&\left( \ln x\right) \left( x\arcsin x+\sqrt{1-x^{2}}\right) -\left( \sqrt{1-x^{2}}+x\arcsin x\right) \\ &&-\sqrt{1-x^{2}}-\frac{1}{2}\ln \frac{\sqrt{1-x^{2}}-1}{\sqrt{1-x^{2}}+1}+C. \\ &=&\left( -1+\ln x\right) \left( x\arcsin x+\sqrt{1-x^{2}}\right) -\sqrt{ 1-x^{2}} -\frac{1}{2}\ln \frac{\sqrt{1-x^{2}}-1}{\sqrt{1-x^{2}}+1}+C. \end{eqnarray*}$$

  • Evaluation of $\int \arcsin x\,dx$ by substitution $$\begin{eqnarray*} \int \arcsin x\,dx &=&\int u\cos u\,du,\quad u=\arcsin x \\ &=&\cos u+u\sin u \\ &=&\sqrt{1-x^{2}}+x\arcsin x+C. \end{eqnarray*}$$
  • Evaluation of $\int \frac{1}{x}\sqrt{1-x^{2}}\,dx$ by substitution and partial fractions $$\begin{eqnarray*} \int \frac{1}{x}\sqrt{1-x^{2}}\,dx &=&-\int \frac{u^{2}}{1-u^{2}}\,du,\qquad u=\sqrt{1-x^{2}} \\ &=&u+\frac{1}{2}\ln \left( u-1\right) -\frac{1}{2}\ln \left( u+1\right) \\ &=&u+\frac{1}{2}\ln \frac{u-1}{u+1} \\ &=&\sqrt{1-x^{2}}+\frac{1}{2}\ln \frac{\sqrt{1-x^{2}}-1}{\sqrt{1-x^{2}}+1}+C. \end{eqnarray*}$$
share|improve this answer
1  
Alternatively, $$\frac{\sqrt{1-x^2}}{x}=\frac{1}{x\sqrt{1-x^2}}-\frac{x}{\sqrt{1-x^2}}$$ –  J. M. Aug 14 '12 at 23:48
    
@J.M. Thanks, with this split the integral becomes $$\int \frac{1}{x}\sqrt{1-x^{2}}\,dx=\sqrt{1-x^{2}}-\text{arctanh}\frac{1}{ \sqrt{1-x^{2}}}+C.$$ –  Américo Tavares Aug 14 '12 at 23:54

Following J.M.'s hint, you may want to prove, again integrating by parts, that $$\int\log x\,dx=x\log x-x+C\,\,,\,\,C=\,\,\text{a constant}$$and perhaps also to note that $$\int \frac{x}{\sqrt{1-x^2}}dx=-\frac{1}{2}\int\frac{-2x}{\sqrt{1-x^2}}dx$$

share|improve this answer

Let I = ∫ ln x * sin−1 x dx,

= x(ln x - 1) * arcsin x - ∫ x(ln x - 1) * 1/√(1 – x^2) dx

= x(ln x - 1) * arcsin x - ∫(ln x - 1) * x / √(1 – x^2) dx

= x(ln x - 1) * arcsin x + (ln x - 1) * √(1 – x^2) – ∫ (1/x) * √(1 – x^2) dx

Call this last integral I1.

Put u = x^2; then du/dx = 2x

∴ I1 = ∫ (1/(2u)) * √(1 – u) * du/dx dx

Put u = 1 – v^2, v ≥ 0; so du/dv = -2v

∴ I1 = ½ ∫ 1/(1 – v^2) * (-2v^2) dv

v^2 / (v^2 – 1) = (v^2 – 1 + 1) / (v^2 – 1) = 1 + 1 / (v^2 – 1)

= 1 + ½ (1/(v – 1) - 1/(v + 1))

So I1 = v + ½ ln (A * (v – 1) / (v + 1)), where A is the arbitrary constant

= √(1 – u) + ½ ln (A * (√(1 – u) – 1) / (√(1 – u) + 1)),

= √(1 – x^2) + ½ ln (A * (√(1 – x^2) – 1) / (√(1 – x^2) + 1)),

Add this to the other parts, and you are done.

I at first thought it could not be done in elementary functions; but there we are!)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.